Hijrah marketing dan tantangan public relation di lembaga keuangan syariah: antara citra religius dan strategi bisnis - Sodiq, Ahmad Fajar (Maliki Interdisciplinary Journal, 2025)
The hijrah phenomenon among millennial and Gen Z Muslims in Indonesia has given birth to a new trend in marketing strategies for Islamic financial institutions known as hijrah marketing. This research aims to analyze the application of the hijrah marketing concept and identify challenges faced by Public Relations in maintaining a balance between religious image and business strategy. The research method used is descriptive qualitative with a literature review approach. The results show that hijrah marketing is effective in building emotional closeness with Muslim customers but faces complex challenges such as the risk of commercializing religion, polarization on social media, and intense market competition. Public Relations plays a strategic role in managing these challenges through honest, educational communication while adhering to Islamic values. This research recommends that Islamic financial institutions strengthen transparency, collaborate with credible figures, and uphold Islamic communication ethics in all hijrah marketing activities.